Recycling plastic waste in cement composites for construction. Engineers Ireland Journal - Pavia, Sara; Kaur, Gurbir (My University, 2019)
Gurbir Kaur and Sara Pavía explore the possibility of raising the amount of recycled plastic (34%) by replacing sand with plastic waste in mortars and concretes, as this would not only reduce plastic incineration and landfill but would also lower raw material extraction with the consequent economy in fuel and carbon emissions
Keywords: Cement; Waste management; Plastic waste; Mortars; Concrete; Construction